2017
DOI: 10.1530/erc-17-0316
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses in the thyroid cancer microenvironment: making immunotherapy a possible mission

Abstract: The incidence of thyroid cancers has been steadily increasing worldwide over the past few decades. Although five-year survival rates for differentiated thyroid cancers are upwards of 90%, clinical outcomes for patients with undifferentiated, recurrent and/or metastatic disease are often dismal despite conventional interventions. As such, there is a demand for novel treatment options. Cancer immunotherapy represents the ultimate form of personalized medicine by leveraging the specificity and potency of a patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 182 publications
(161 reference statements)
0
25
0
Order By: Relevance
“…Nevirapine, as an immunomodulator, has been shown to inhibit the secretion of cytokine IL‐6 in HIV‐infected patients . Accumulating studies suggest that thyroid cancer is also an autoimmune disease . We found that nevirapine could inhibit IL‐6 mRNA expression in thyroid cancer by RT‐PCR.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Nevirapine, as an immunomodulator, has been shown to inhibit the secretion of cytokine IL‐6 in HIV‐infected patients . Accumulating studies suggest that thyroid cancer is also an autoimmune disease . We found that nevirapine could inhibit IL‐6 mRNA expression in thyroid cancer by RT‐PCR.…”
Section: Discussionmentioning
confidence: 72%
“…29 Accumulating studies suggest that thyroid cancer is also an autoimmune disease. [30][31][32] We found that nevirapine could inhibit IL-6 mRNA expression in thyroid cancer by RT-PCR. To elucidate the mechanism underlying the effects of IL-6 in thyroid cancer, we assessed the expression of its downstream genes.…”
Section: Discussionmentioning
confidence: 84%
“…These not only include remodeling of tumor niche (e.g., reorganization of extracellular matrix and formation of blood vessels) but also production of cytokines and growth factors that increase motility and invasiveness of cancer cells as well as decrease their sensitivity to pro-death factors [40,41]. Immune cells have an obvious role also in the development and progression of thyroid cancers [42,43]. On the other hand, phenotypic differences between a primary tumor and its lymph node metastases could also reflect invasionrelated features of metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…further research and treatment of thyroid cancer in microenvironment are required. The value of ARHI and Beclin1 in the study of the expression level of thyroid cancer is very high, mainly because the tumor cells can be killed through the function of the immune system; the microenvironment in the body of cancer patients is rich in immune cells, and immunotherapy is the ultimate treatment (25). The effects of ARHI and Beclin1 genes on the formation of thyroid tumor cells and the related mechanisms were also analyzed at the histological level of human thyroid cancer, which provided theoretical basis for the targeted treatment of thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%